Services and metropolitan development International perspectives - P.W.Daniels (Routledge, 1991)
The dynamics of national and international urban systems, as well as individual metropolitan areas, are now more closely connected than ever with the decisions and actions of firms and institutions in the service sector. One of the clearest implications of this new phenomenon is the way in which trade in services (much of which has its origins and destinations in large cities around the world) has recently become a prominent and contentious issue in the Uruguay Round of Negotiations for the General Agreement on Tariffs and Trade (GATT).